An effective and simplified DO-stat control strategy for production of rabies glycoprotein in Pichia pastoris - Picotto, Leandro Daniel (2017)
The glycoprotein (G-protein) of rabies virus is responsible for viral attachment to the host cell surface and induces virus neutralization antibodies. In the present study, the G-protein gene of rabies virus CVS strain was cloned, sequenced and expressed in the yeast, Pichia pastoris, as a secreted protein, using a simplified DO-stat control feeding strategy. This strategy involves the addition of methanol when the dissolved oxygen (DO) level rises above the setpoint avoiding methanol accumulation and oxygen limitation. The G-protein expression was evaluated by SDS-PAGE, ELISA, and western blot assays. Like native G-protein, the recombinant G-protein was found reactive when it was challenged against specific antibodies. The data indicate that the recombinant G-protein can be easily expressed and isolated, and may be useful as a safe source in the production of diagnostic kits and subunit vaccines to prevent rabies.